1991
DOI: 10.3109/10428199109068123
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Heme Analogues on Hematopoiesis in Lymphoproliferative Disorders

Abstract: Anemia is a common characteristic of lymphoproliferative disorders (LPD) and the impairment of blood formation in these disorders is not fully understood. Heme synthesis and the heme degradative enzyme heme oxygenase are critical to hematopoietic differentiation and disturbances may contribute to anemic states. Tin protoporphyrin (SnPP) is a potent inhibitor of heme oxygenase, and has proven to be a useful clinical agent. Bone marrow cells from seven patients with LPD were studied for their in vitro hemopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Effect of Metalloporphyrins on Human Bone Marrow Growth. We have previously shown that heme enhances in vitro erythropoiesis (1,15). We therefore examined the dose effects of ZnPP and SnPP on human bone marrow erythroid colony growth (CFU-E, BFU-E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Effect of Metalloporphyrins on Human Bone Marrow Growth. We have previously shown that heme enhances in vitro erythropoiesis (1,15). We therefore examined the dose effects of ZnPP and SnPP on human bone marrow erythroid colony growth (CFU-E, BFU-E).…”
Section: Resultsmentioning
confidence: 99%
“…Heme analogues were obtained from Porphyrin Products (Logan, UT) and included tin mesoporphyrin (SnMP), tin protoporphyrin (SnPP), zinc mesoporphyrin (ZnMP), ZnPP, CrMP, protoporphyrin IX (PPIX), mesoporphyrin IX (MPIX), and heme. The heme analogues, except for ZnMP and ZnPP, were prepared and added to cultures as described (1). Zinc porphyrins were first dissolved in propylene glycol to give a final concentration of 10% (vol͞vol) and then prepared as described (1).…”
Section: Preparation Of Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, heme and certain other metalloporphyrins stimulate the immune system and enhance erythropoiesis (4,5). Heme, as well as the synthetic heme analog tin protoporphyrin, significantly enhances bone marrow erythroid progenitor proliferation and differentiation in lymphoproliferative disorders (6). It has also been shown that heme and other synthetic heme analogs significantly inhibit HIV-1 RT activity in a noncompetitive manner with respect to deoxythymidine triphosphate and markedly enhance the inhibitory effect of AZT-TP on HIV-1 RT (7).…”
mentioning
confidence: 99%